Cyanotoxin-producing bloom of Anabaena flos-aquae, Anabaena discoidea and Microcystis aeruginosa (Cyanobacteria) in Nyanza Gulf of Lake Victoria, Kenya - Krienitz, L.; Ballot, A.; Wiegand, C.; Kotut, Kiplagat; Codd, G.A.; Pflugmacher, S. (My University, 2002)
A bloom of Anabaena flos-aquae, Anabaena discoidea and Microcystis aeruginosa, was characterized in Nyanza Gulf of Lake Victoria, near Kisumu, Kenya. According to classical literature data, A. discoidea was considered to be endemic to the Great Lakes of Africa. Its morphological characteristics are described and discussed in relation to A. flos-aquae. The two samples investigated contained the cyanobacterial toxins, microcystin-LR, -RR, -LA and -LF.
Keywords: Anabaena flos-aquae; Anabaena discoidea; Microcystis aeruginosa